Sinusoidal Bragg grating based on hybrid metal insulator metal plasmonic waveguide. (1st November 2018) - Chitimireddy, Sindhura; Sharma, Prateeksha; Vishwakarma, Dinesh Kumar
Abstract : This is the first report on 3D sinusoidal Bragg grating structure based on hybrid metal insulator metal (HMIM) plasmonic waveguide. The proposed structure has a gradual change in the refractive index rather than an abrupt change providing excellent filtering characteristics. The device is studied at an operating wavelength of 1.55 μm. The results are based on numerical simulations performed using the software CST microwave studio suite. The transmission characteristics show more than 80% transmission in the passband and near zero transmission in the rejection band. The proposed structure reduces the scattering losses and a wide bandgap of 0.387 μm is achieved. The proposed structure has a track length of 3.784 μm for 11 cells, which is very less compared to previous reports allowing large‐scale integration of photonic devices. A microcavity is also formed and its resonance is investigated by introducing a defect length of 0.217 μm in the periodic structure. A peak transmission of 50% and a narrow resonance bandwidth of 0.029 μm are achieved at 1.55 μm resonance wavelength. The quality factor which defines the energy stored in the cavity is Q = 53.